Preservation Strategy of Malay Folklore in West Kalimantan as a Protection Indonesian Cultural Heritage in the Modernization Era - Kusnita, Sri; Suwandi, Sarwiji; Rohmadi, Muhammad; Eko Wardani, Nugraheni (Opción, 2019)
This study aims to describe the preservation strategy of Malay folklore in West Kalimantan as a realization of awareness toward Indonesian cultural heritage. Pro- tection of folklore needs to do because folklore is a medium for former society to deliver the values of kindness that can be used by young generations for a behav- iour reference. The method employed was a descriptive qualitative method. Data collection technique employed FGD. The preservation strategy of Malay folklore in West Kalimantan can be carried out through Inventory of Folklore, alternative Learning Material, and bertutur (storytelling competition) in Malay cultural festi- val, and local government regulations.